Determination of flavonoid levels of Macaranga gigantea and its activity as antioxidants - Samsul Hadi; Dian Ekowati; Amalia Khairunnisa (Jurnal Pijar Mipa, 2023)
One of the ways to prevent generative diseases is by using natural antioxidant compounds. The flavonoid compounds in the flower parts of M. gigantea have a role in antioxidants. Thus the study aimed to test the antioxidant activity and flavonoid levels of M. gigantea flowers. The antioxidant test was carried out by UV-vis spectrophotometry using 2,2-diphenyl-1-picrylhydrazyl and flavonoid assay using 10% aluminum chloride and potassium acetate, both tests using quercetin as a comparison. The results of this test obtained IC50 antioxidants 145,725 ± 3.858 ppm, and flavonoids were 1,860 ± 0.007% w/w eq quercetin. The conclusion from the experiments that have been carried out is that M. gigantea flowers have moderate antioxidant abilities.